Predictors of quality of life among informal caregivers of patients with advanced cancer in palliative care: a cross-sectional study - Weeratunga, Eranthi; Goonewardena, Sampatha; Meegoda, Lalitha (International Journal Of Community Medicine And Public Health, 2025)
Background: Family members and informal caregivers (ICs) have been suffering many problems, issues, and burdens, which impact the quality of life (QoL). Improving the QoL of ICs is a key aspect of palliative care (PC). This study aimed to determine the predictors of QoL among ICs of patients with advanced cancer in PC. Methods: This cross-sectional study included 422 ICs who were selected conveniently and attended the PC unit and clinics at Apeksha Hospital, Maharagama, Sri Lanka. An interviewer-administered questionnaire, which included socio-demographic and clinical characteristics, was used to collect data. QoL of ICs was assessed using the validated WHOQOL-BREF scale; higher scores indicated higher QoL. Descriptive and inferential statistics were used. Results: The mean±SD age of the ICs was 43.13±14.92. The majority of ICs and patients were female. The mean WHOQOL‐BREF domain scores of ICs were 26.56±12.30 for physical health, 20.64±3.23 for psychological status, 10.03±1.60 for social relations, and 24.76±3.72 for the environmental domain. Predictors of QoL among ICs were age (p<0.01), religion (p<0.01), education (p<0.05), family income (p<0.01), care level (p<0.01), physical illnesses (p<0.01), emotional strain (p<0.05), self-reported general health (p<0.01), medical conditions (p<0.05), psychological conditions (p<0.01), comorbidities (p<0.05), and family/friend support (p<0.05). Conclusions: The physical QoL was considerably high, while all domains among ICs were impaired. It is recommended to consider the predictors of QoL of ICs comprehensively who live in third-world developing countries. Sri Lankan healthcare professionals must ensure that ICs have overall well-being and receive the proper support/resources to care for their patients.